THE VALUE RELEVANCE OF FINANCIAL INSTRUMENTS RISK DISCLOSURE UNDER IFRS 7 IN INDONESIAN BANKING SECTOR - Razafinandrasana Cynthia (Diponegoro Journal of Accounting, 2022)
The purpose of this thesis is “to examine the impact of IFRS 7’s risk disclosure requirements on investors in the Indonesian banking sector”. This research is based on data on various types of financial risk from the Indonesian market banking sector, including: “credit, liquidity, and market risks, as defined by IFRS 7”. The purpose of this research is “to determine the value relevance of financial instruments risk disclosure from the perspective of users in the Indonesian banking industry in accordance with IFRS 7 recommendations; to determine whether the information on financial risks required by IFRS 7 is relevant to investors in order to support their investment decisions”; and “to analyze the impact of financial instrument risk disclosure required by IFRS 7 in the Indonesian banking system on investors”. This research was aided by agency theory. This study’s population is the banking sector on the Indonesian Stock Exchange from 2018 to 2019. The total number of companies included in the research sample is 41. The analysis of this research included descriptive statistics, Pearson correlation, and Ordinary Least Square (OLS) regression. Our analyses confirm that: “the qualitative financial disclosure index (QLFDI) has a positive effect on the share price of a bank, whereas the quantitative financial disclosure index (QTFDI) has a negative effect on the share price of a bank; thus, the qualitative financial disclosure index recommended by IFRS 7 is relevant”.